2007
DOI: 10.1111/j.1472-765x.2006.02096.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and growth of Listeria monocytogenes in naturally contaminated cold-smoked salmon

Abstract: Aim:  To investigate Listeria monocytogenes contamination and behaviour in naturally contaminated French cold‐smoked salmon (CSS). Method and Results:  Between 2001 and 2004, L. monocytogenes was detected in 104 of 1010 CSS packs, produced by nine French plants, with different prevalence (from 0% to 41%). The initial contamination, measured with a sensitive filtration method, was low (92% of contaminated products below 1 CFU g−1) and growth was limited. Conclusion:  Growth was consistent with results of a pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 22 publications
(49 reference statements)
2
41
1
6
Order By: Relevance
“…In a survey on the prevalence of L. monocytogenes in RTE foods at retail in Sweden in 2010, the pathogen was detected in 12 % of 558 smoked and gravad fish samples at the end of shelf-life (Lambertz et al, 2012). Beaufort et al (2007) followed-up nine representative cold smoked salmon producing sites in France from 2001 to 2004, and found a mean prevalence of 10.3 % at the end of shelf-life in their products. Corcoran et al (2006) have indicated the potential for persistence of L. monocytogenes in smoked salmon production environments.…”
mentioning
confidence: 99%
“…In a survey on the prevalence of L. monocytogenes in RTE foods at retail in Sweden in 2010, the pathogen was detected in 12 % of 558 smoked and gravad fish samples at the end of shelf-life (Lambertz et al, 2012). Beaufort et al (2007) followed-up nine representative cold smoked salmon producing sites in France from 2001 to 2004, and found a mean prevalence of 10.3 % at the end of shelf-life in their products. Corcoran et al (2006) have indicated the potential for persistence of L. monocytogenes in smoked salmon production environments.…”
mentioning
confidence: 99%
“…Next, Mejlholm and Dalgaard [26] modelled the effect of diacetate and lactate against L. monocytogenes in vacuum packaged or modified atmosphere packaged (MAP) CSS, marinated salmon, cold-smoked Greenland halibut, marinated Greenland halibut, and gravad salmon. About the same time, Beaufort et al [27] developed a model that also included the effects of microbial competition on growth of L. monocytogenes. After this, Hwang [28] evaluated the effects of salt, smoke compounds, storage temperature, and their interactions on the growth of L. monocytogenes in CSS, developing two models to describe the lag phase duration and growth rate in salmon containing 0 to 8% salt and 0 to 34 ppm of phenol at storage temperatures of 4 to 25 • C. About the same time, Pouillot et al [29] developed a model to predict exposure of consumers of French CSS to L. monocytogenes, which takes into account bacterial growth and interactions with other microflora.…”
Section: Growth Of Listeria Monocytogenes In Lightly Preserved Seafoodmentioning
confidence: 99%
“…The outbreak of listeriosis related to vacuum packed gravad and cold-smoked fish was described in at least eight human cases for 11 months in Sweden [42]. Cold-smoked and gravad rainbow trout (Oncorhynchus mykiss) and salmon (Salmo salar) have been focused on during recent years as potential sources of infection with L. monocytogenes and there are several report on isolation of this food borne pathogen from fish-processing plants environments [14,37,39,[43][44][45]. Seafood treatment is necessary to prevent food-borne illness.…”
Section: Listeria Monocytogenes Staphylococcus Aureus Clostridium Pmentioning
confidence: 99%
“…L. monocytogenes is a serious threat to consumer health and safety and has been implicated in several deadly outbreaks around the world [1,2]. This organism is halotolerant (up to 28% w/v for short periods), resistant to freezing temperatures, can grow and multiply during refrigeration, where other competing organisms cannot, and is able to survive at low water activity (aw) [9,14,37]. L. monocytogenes is widely distributed in the general environment including fresh water, coastal water and live fish from these areas.…”
Section: Listeria Monocytogenes Staphylococcus Aureus Clostridium Pmentioning
confidence: 99%
See 1 more Smart Citation